Upaya Peningkatan Kesehatan Gigi dan Mulut Anak Pra Sekolah - Lisnayetti; Nova Herawati; Syukra Alhamda (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
Preschool-aged children are among the groups most vulnerable to oral health problems, particularly dental caries, due to their frequent consumption of cariogenic foods and lack of proper knowledge and habits in maintaining oral hygiene. A preliminary survey at Raudhatul Athfal (RA) Ar Rahmah Bukittinggi showed that most children were unaware of the correct toothbrushing techniques and often consumed sweet foods. The method of this activity is dental health education, toothbrushing demonstration, and dental examinations were conducted for the students. This activity aimed to increase the knowledge and behavior of students in maintaining oral health. The results showed that the children were enthusiastic in participating and most were able to practice correct toothbrushing techniques. Dental examinations revealed an average caries experience of 5.47, with each child having 5-6 carious teeth, indicating a poor caries condition among RA Ar Rahmah students..